Analysis the correlation of anemia knowledge and menu acceptability on hemoglobin levels in female santri at Pesantren Dar El Hikmah Pekanbaru: A cross-sectional study - Elvy Ramadani; Lilik Kustiyah; Ikeu ekayanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Anemia is a common health issue among adolescent girls, including female students at boarding schools, and it was found that the prevalence of anemia in one boarding school in Indonesia was 38%. Anemia is indicated by low hemoglobin levels caused by insufficient intake of iron and other nutrients. This study aimed to analyze the correlation between anemia knowledge, menu acceptability, and nutrient intake and hemoglobin levels in female students. This study used a cross-sectional design conducted at Dar El Hikmah Islamic Boarding School Pekanbaru, with a total of 105 female MA students who were selected purposively based on inclusion and exclusion criteria. Data were collected from November to December 2024. Anemia knowledge was measured using a questionnaire, menu acceptability estimated by leftover food, nutrient intake obtained from 2 × 24 h food recall, and hemoglobin (Hb) level measured using easy touch GCHb. Data were analyzed using the rank-Spearman test. The results showed that most subjects (53,3%) had anemia or Hb levels <12 g/dL. There was a significant negative correlation between the acceptability of the breakfast menu (r=−0,366; p=<0,001), lunch (r=−0,445; p=<0,001), and dinner (r=−0,516; p=<0,001), and a positive correlation between anemia knowledge (r=0,254; p=0,009); protein (r=0,235; p=0,019), iron (r=0,200; p=0,040), vitamin C (r=0,349; p=<0,001), vitamin B9 (r=0,471; p=<0,001), and vitamin B12 intake (r=0,221; p=0,023) with Hb level. In conclusion, knowledge is needed to prevent anemia, and the quality of school menus must be improved to increase acceptance and nutrient intake.